The impact of the level of development of education and law on the economic potential of the country - Tkach , Mykola; Loishyn , Anatolii; Kondratiuk, Serhii (Social Development and Security, 2020)
The article is of interest to experts in the economic field who study the problems of economic potential of the country. The purpose of the article is to study the patterns in the development of economic potential of the country and its dependence on the degree of development of education, science and law in the state. The set scientific task was solved by comparing the economic development of some countries and the development of their education and law. In the process of achieving the goal of the study, the following methods of scientific knowledge were used: historical analogy, analysis, synthesis, induction, deduction, system approach. The analysis of sources shows that the impact of education and the right to economic development of countries is given great attention to world-renowned economists since the beginning of the XVII century. and ending in the present tense. This scientific work shows that the development of education and its widespread dissemination is a prerequisite for the development of science and liberalization of law, and in the aggregate and a prerequisite for economic development. On the example of such developed world countries as the USA, Great Britain, France, Germany, etc. identified certain factors that contributed to the development of methods of knowledge transfer and development in these countries. An analysis of the ranking of world universities, the world index of justice and economic well-being of some countries.